2006
DOI: 10.1111/j.1463-1326.2006.00647.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled insulin as adjunctive therapy in subjects with type 2 diabetes failing oral agents: a controlled proof‐of‐concept study

Abstract: In subjects with type 2 diabetes inadequately controlled by oral agents, preprandial administration of INH delivered by a MDI provided a comparable metabolic control to bedtime GLA and did not show any safety concerns during a 4-week treatment. These results warrant a more extensive investigation of preprandial treatment with INH in longer term studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The propellant mixtures were found to improve the aerosol performance over the pure propellant. This formulation has been shown to provide comparable blood glucose control to subcutaneous insulin injections in type 2 diabetic patients [69]. This formulation has been shown to provide comparable blood glucose control to subcutaneous insulin injections in type 2 diabetic patients [69].…”
Section: Metered Dose Inhalersmentioning
confidence: 93%
See 1 more Smart Citation
“…The propellant mixtures were found to improve the aerosol performance over the pure propellant. This formulation has been shown to provide comparable blood glucose control to subcutaneous insulin injections in type 2 diabetic patients [69]. This formulation has been shown to provide comparable blood glucose control to subcutaneous insulin injections in type 2 diabetic patients [69].…”
Section: Metered Dose Inhalersmentioning
confidence: 93%
“…An aqueous solution of the protein and surfactant was first freeze dried to produce the required particles, which were subsequently suspended in HFA-134a alone or a mixture of this propellant and dimethylether [67] or ethanol [68]. Kos Pharmaceuticals (Florida, USA) has developed an insulin MDI suspension in HFA-134a [69,70]. Kos Pharmaceuticals (Florida, USA) has developed an insulin MDI suspension in HFA-134a [69,70].…”
Section: Metered Dose Inhalersmentioning
confidence: 99%
“…The very popular and also highly unstable human insulin has also been formulated as a suspension in HFA-134a propellant by Kos Pharmaceuticals (Weston, FL, USA) which has also been tested in type II diabetics to result in a rapid onset of action and comparable blood glucose levels to insulin glargine at base line and after 28 days when administered pre-prandially. This clearly showed that the structural and functional integrity of insulin was not compromised while remaining suspended in HFA134a [ 79 ].…”
Section: Description Of Pfizer’s Mrna Covid-19 Vaccine Formulation Bn...mentioning
confidence: 99%
“…The proof of concept for inhaled insulin, a dry powder aerosol delivery system of human insulin, was initially examined in an early phase II study on 69 patients with type 2 diabetes who were randomized to a 3-month treatment period of either continued oral agents alone (sulfonylurea and/ or metformin) or in combination with 1 or 2 puffs of inhaled insulin before meals (121). The inhaled insulin doses were titrated based on glucose testing four times daily.…”
Section: The Mechanical Barriermentioning
confidence: 99%